Peran Masyarakat Adat Kelurahan Sedinginan Kecamatan Tanah Putih Kabupaten Rokan Hilir dalam Penyelesaian Sengketa Perkawinan - Asrul Ariadi; Rika Lestari; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Indonesian nation is a nation consisting of various tribes. The hundreds, so that itslegal culture and also varied. Such legal in Indonesia called Customary Law, marriagedisputes that occur in indigenous village land sedinginan white districts downstream districtsrokan completed by ninik Mamak. Based on the description above, the writer interested inconducting research with the title